2020
DOI: 10.1177/0886260520909185
|View full text |Cite
|
Sign up to set email alerts
|

Child Safety Matters: Randomized Control Trial of a School-Based, Child Victimization Prevention Curriculum

Abstract: Recognizing the potential of classrooms as a context for identifying and addressing child victimization, several U.S. states now mandate the inclusion of child abuse prevention in school curricula. There are, however, a limited number of evidence-based and developmentally appropriate curricula designed for elementary. This study utilized a randomized control trial (RCT) design to evaluate the knowledge acquisition of children who received the Monique Burr Foundation’s Child Safety Matters curriculum, a program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
1
8
0
5
Order By: Relevance
“…The study findings show small gains in knowledge from pre-to post-testing across all grades and both genders, though with ceiling effects in pre-test scores. These results are consistent with Bright et al (2020) and Jones and Ah Jung (2015) who also found gains in knowledge from pre-to post-testing with the CSM program but with different populations of students. However, both of those studies used researcher-created measures, while the assessment of child knowledge in the current study was part of the CSM curriculum.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study findings show small gains in knowledge from pre-to post-testing across all grades and both genders, though with ceiling effects in pre-test scores. These results are consistent with Bright et al (2020) and Jones and Ah Jung (2015) who also found gains in knowledge from pre-to post-testing with the CSM program but with different populations of students. However, both of those studies used researcher-created measures, while the assessment of child knowledge in the current study was part of the CSM curriculum.…”
Section: Discussionsupporting
confidence: 91%
“…In the only published randomised control trial (RCT) of the CSM program, Bright et al (2020) implemented the CSM program in the state of Florida with 1176 students from 72 classrooms. Schools were matched in pairs and randomly assigned to either receive the program or be in a wait‐list control.…”
Section: Child Safety Mattersmentioning
confidence: 99%
“…Divergindo das condutas e posturas assumidas pelos professores que participaram dessa pesquisa, estudos apontam a escola como cenário propício para implementar forças que impulsionam a proteção à criança em risco ou situação de violência (Bright, et al, 2020;Del Campo & Fávero, 2020;Cordeiro, et al, 2019), e os professores como atores sociais importantes para o adequado funcionamento da rede (Macedo, et al, 2019;Wilkinson, et al, 2019).…”
Section: Discussionunclassified
“…A literatura indica como estratégias capazes de promover a prevenção da violência contra a criança: implementar atividades educativas que abordem a temática (Bright, et al, 2020;Segura & González, 2020); assumir o papel na rede, especialmente considerando a relevância da escola como cenário para a identificação e notificação da violência, haja vista que, depois da família, ela torna-se o segundo espaço social em que a criança permanece maior parte de seu tempo (Ferreira, Côrtes & Gontijo, 2019;Elsen, et al, 2011); integrar-se à rede, tornando explícitas as relações com os órgãos de defesa das crianças (Elsen, et al, 2011); promover ambientes em que as crianças possam se expressar (World Health Organization, 2019; Fundo das Nações Unidas para a Infância, 2019); e envolver os pais e comunidade em atividades de prevenção da violência; treinamento para conhecerem os tipos mais comuns de violência, como identificar, fatores de risco e estratégias para seu enfrentamento, incluindo denúncia e acompanhamento dos casos junto a outras unidades de proteção (World Health Organization, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation